Providing dementia education with augmented reality: a health sciences and medicine feasibility pilot study - Cindy Jones; Daniel Khalil; Karanjot Mander; Alexandra Yeoh; Christian Moro (Association for Learning Technology, 2022)
Understanding the key physiology and anatomy of the brain, and the mechanisms underlying dementia, represents essential components within a medical curriculum. This study assessed the implementation feasibility of an augmented reality (AR) three-dimensional (3D) brain visualisation learning mode and the knowledge improvements in medical students when compared to a text-based pamphlet. The pamphlet group learnt from a double-sided information pamphlet, while the AR group used an AR app. In AR, participants held a cube in front of the camera on the tablet, rendered on-screen as a 3D brain model, and received a narrated lesson containing the same information as the pamphlet verbatim. Both resources were also evaluated for perceived usefulness via pre-post tests and written survey. A total of 24 students participated in the study. A significant overall difference in knowledge scores (p < 0.001) was found for all participants but without significant differences between groups. Prior education was a significant covariate for pre-post change (p = 0.016) across all participants but had no impact on group outcomes. Positive feedback was received on both resources where the majority perceived them as easy to use, enjoyable, and helped develop their knowledge of dementia. Both the text-based pamphlet and AR delivery modes improved knowledge, although neither was significantly superior to the other. However, the AR lesson was perceived highly for learning, and has the potential for implementation within a medical programme.